AWS networking cookbook : powerful recipes to master the pain points of optimizing your VPC - Das, Satyajit; Modi, Jhalak (Packt Publishing, 2017)
Over 50 recipes covering all you need to know about AWS networking About This Book Master AWS networking concepts with AWS Networking Cookbook. Design and implement highly available connectivity and multi-regioned AWS solutions A recipe-based guide that will eliminate the complications of AWS networking. A guide to automate networking services and features Who This Book Is For This book targets administrators, network engineers, and solution architects who are looking at optimizing their cloud platform's connectivity. Some basic understanding of AWS would be beneficial. What You Will Learn Create basic network in AWS Create production grade network in AWS Create global scale network in AWS Security and Compliance with AWS Network Troubleshooting, best practices and limitations of AWS network Pricing model of AWS network components Route 53 and Cloudfront concepts and routing policies VPC Automation using Ansible and CloudFormation In Detail This book starts with practical recipes on the fundamentals of cloud networking and gradually moves on to configuring networks and implementing infrastructure automation. This book then supplies in-depth recipes on networking components like Network Interface, Internet Gateways, DNS, Elastic IP addresses, and VPN CloudHub. Later, this book also delves into designing, implementing, and optimizing static and dynamic routing architectures, multi-region solutions, and highly available connectivity for your enterprise. Finally, this book will teach you to troubleshoot your VPC's network, increasing your VPC's efficiency. By the end of this book, you will have advanced knowledge of AWS networking concepts and technologies and will have mastered implementing infrastructure automation and optimizing your VPC. Style and approach A set of exciting recipes on using AWS Networking services more effectively.